PRODUKSI KESEMEK NON-ASTRIGENSI DENGAN PERLAKUAN HOT WATER TREATMENT DAN APLIKASI KOH - Rozana Rozana; Lorine Tantalu (Journal of Food Technology and Agroindustry, 2019)
The treatment that is often used by farmers and persimmon collectors for local consumption in Indonesia is by immersion in quicklime (building lime) so as to produce powdery persimmon fruit that covers the color of mature persimmon fruit which is usually bright yellow to orange. This study aims to obtain the best treatment to produce persimmon according to the quality requirements desired by consumers through KOH application treatment to obtain bright and attractive colors, Hot Water Treatment (HWT) for relieving soreness and disinfecting pests, and soaking in lime solution to maintain texture fruit. The experimental design of this study was Factorial Randomized Group Design with 2 factors, namely the immersion time of hot water 46 0C (HWT) and KOH application. The first factor has three levels of treatment, namely without HWT (A1), 5 minutes (A2), and 10 minutes (A3). The second factor has two levels, namely without applying (B1) and applying KOH (B2). Quality observations include measurements of weight loss, color, hardness, and total dissolved solids. The 5-minute HWT treatment and KOH application gave a significant effect on several parameters, namely weight loss, hardness, and total dissolved solids but were unable to extend the shelf life of persimmon.